Collaborative structure and post‐mobility knowledge spillovers: A dyadic approach - Tzabbar, Daniel; Lee, Jeongsik (Jay); Seo, Donghwi (Josh) (Strategic Management Journal, 2022)
Research Summary How does the dyadic collaborative structure between the hiring firm and the losing firm influence knowledge spillovers following an employee's move? We demonstrate that knowledge spill‐ins (to the hiring firm) and spill‐backs (to the losing firm) are the greatest when a firm with a strong collaborative density hires an employee from another firm that too has a strong collaborative density. Furthermore, such a dyadic combination results in the greatest degree of access to the broader knowledge of the other firm. By considering the role of relative collaborative structures in post‐mobility knowledge‐building activities, we inform the extant literature on the importance of this factor. In doing so, we invite scholars to take a more holistic view of the risks and benefits associated with “learning by hiring.” Managerial Summary Firms interested in acquiring the knowledge of other firms through employee recruitment face a dilemma. To best integrate the knowledge brought in by new employees, firms must encourage extensive collaboration between existing employees and new hires. However, such a dense collaboration exposes firms to potential knowledge spill out through these new hires, which may undermine their competitive edge. Firms that lose employees face the reverse dilemma. Accordingly, managers and practitioners should realize that not all recruitments may result in net knowledge gains. Our findings strongly suggest that where a firm hires from also matters, not just who it hires, thereby offering a practical insight for organizations in properly assessing the utility of hiring an employee, particularly in consideration of their relative collaborative structures.